Preparedness of the Medan Center for Quarantine and Health (BBKK) in Preventing and Controlling New Emerging Diseases and Potential Epidemic Infectious Diseases at Belawan Port - Manurung, Paulus; Otniel Ketaren; Jasmen Manurung; Kesaktian Manurung; Mido Ester Sitorus (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
In recent decades, the world has witnessed the emergence of various infectious diseases that have had serious impacts on global public health. One institution that plays an important role in preventing the spread of infectious diseases across countries is the Balai Besar Kekarantinaan Kesehatan (BBKK). This research aims to provide an in-depth picture of BBKK Medan's preparedness in preventing new diseases and potential outbreaks of infectious diseases. This research uses a qualitative approach. The research informants were the Head of BBKK Medan, head of team II, functional entomologist, functional epidemiologist of BBKK Medan. The selection of informants was carried out using a purposive sampling technique. The research results show that BBKK Medan implements several strategic steps in preventing and preventing new diseases and potential outbreaks of infectious diseases, namely: carrying out routine evaluation monitoring, increasing human resource capacity, cross-sector coordination, implementing health protocols, carrying out vector prevention, conducting surveillance, and increasing public awareness. The obstacles faced by BBKK Medan in carrying out health quarantine duties are a shortage of experts who have special competence in the field of quarantine, low compliance with procedures, limited equipment and high human mobility. Factors that influence the success or failure of efforts to prevent and control infectious diseases at BBKK Medan include the availability of an adequate budget, clear and consistent regulations, effective cooperation or coordination between government agencies and related institutions. Strategies that can increase the effectiveness and preparedness of BBKK Medan are by carrying out strict supervision at country entry points, increasing human resource capacity, increasing cross-sectoral coordination, using the latest technology, strengthening community-based surveillance. It is recommended that BBKK Medan increase the effectiveness of controlling infectious diseases through implementing an integrated surveillance system at country entry points